The Effect of Aging on the Dynamics of Reactive and Proactive Cognitive Control of Response Interference - Xiang, Ling; Zhang, Baoqiang; Wang, Baoxi; Jiang, Jun; Zhang, Fenghua; Hu, Zhujing (Frontiers in Psychology, 2016)
A prime-target interference task was used to investigate the effects of cognitive aging on reactive and proactive control after eliminating frequency confounds and feature repetitions from the cognitive control measures. We used distributional analyses to explore the dynamics of the two control functions by distinguishing the strength of incorrect response capture and the efficiency of suppression control. For reactive control, within-trial conflict control and between-trial conflict adaption were analyzed. The statistical analysis showed that there were no reliable between-trial conflict adaption effects for either young or older adults. For within-trial conflict control, the results revealed that older adults showed larger interference effects on mean RT and mean accuracy. Distributional analyses showed that the decline mainly stemmed from inefficient suppression rather than from stronger incorrect responses. For proactive control, older adults showed comparable proactive conflict resolution to young adults on mean RT and mean accuracy. Distributional analyses showed that older adults were as effective as younger adults in adjusting their responses based on congruency proportion information to minimize automatic response capture and actively suppress the direct response activation. The results suggest that older adults were less proficient at suppressing interference after conflict was detected but can anticipate and prevent inference in response to congruency proportion manipulation. These results challenge earlier views that older adults have selective deficits in proactive control but intact reactive control.